2019
DOI: 10.1002/ar.24222
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Inhibits Breast Tumor Growth and Angiogenesis by Regulating VEGF/VEGFR2 and p38MAPK Signaling Pathways

Abstract: Tumor angiogenesis is an important cause of tumor growth and metastasis. Myricetin is a flavonoid component used in traditional Chinese medicine that has been demonstrated to have anticancer activity. However, to the best of our knowledge, the effect of myricetin on tumor angiogenesis remains unknown. The present study reports the identification of myricetin as a potential chemopreventive agent by reason of its inhibition of tumor angiogenesis and demonstrates the anticancer effects of myricetin in vivo. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Growing evidence has indicated that the generation of ROS could lead to cell apoptosis accompanied with triggering the activation of mitogen activated protein kinases (MAPKs), which include extracellular regulated protein kinase (ERK), c-Jun N-terminal kinase (JNK), and p38MAPK ( 29 ). p38MAPK was regarded as one of the most important intracellular survival signal and frequently activated in diverse cancers, such as breast ( 30 ), liver ( 31 ), and lung ( 32 ) cancers, suggesting its role in cancer progression. Generally, suppression of p38MAPK pathway could result in cell cycle arrest, which was commonly regulated by cyclins (cyclin D1 and cyclin B1) and tumor suppressor protein p53.…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence has indicated that the generation of ROS could lead to cell apoptosis accompanied with triggering the activation of mitogen activated protein kinases (MAPKs), which include extracellular regulated protein kinase (ERK), c-Jun N-terminal kinase (JNK), and p38MAPK ( 29 ). p38MAPK was regarded as one of the most important intracellular survival signal and frequently activated in diverse cancers, such as breast ( 30 ), liver ( 31 ), and lung ( 32 ) cancers, suggesting its role in cancer progression. Generally, suppression of p38MAPK pathway could result in cell cycle arrest, which was commonly regulated by cyclins (cyclin D1 and cyclin B1) and tumor suppressor protein p53.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, myricetin possesses a backbone very similar to that of other flavonols that have been presented above, including quercetin, which seems to be related with a relevant antiangiogenic activity of the compound [289]. The role of myricetin as an angiogenesis inhibitor has been studied in endothelial cells, revealing a mechanism that involves induction of apoptosis and suppression of PI3K/Akt/mTOR signaling pathways [290], and a reduction in VEGF-A/VEGFR2 axis and in p38-MAPK survival pathway [291].…”
Section: Grapesmentioning
confidence: 88%
“…Myricetin acts as a potent inhibitor of the known antiapoptotic signaling pathways ERK1/2 in lung cancer cell lines and PI3K in pancreatic (Phillips et al, 2011), cervical and lung cancer cell lines. In breast cancer, myricetin can inhibit angiogenesis induced by VEGF and p38/MAPK signaling (Zhou, Mao, Li, Qi, & He, 2019). It has been reported that myricetin can inhibit proliferation and induce apoptosis of HCC cells by inducing LATS1/2 activation, YAP phosphorylation and degradation, survival inhibition and caspase 3 cleavage (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%